2021
DOI: 10.14260/jemds/2020/183
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Evaluate the Combined Use of Alvarado Score and Imaging for Diagnosis of Acute Appendicitis

Abstract: Thyroid pathology is very common in general population, even when on inspection no abnormality is detected, nodules are seen on ultrasound sonography (USG). We are describing importance of peripheral halo sign in the diagnosis of benign nodules. Among all the endocrine gland lesions noted in India, thyroid lesion is the most common. In about 19 - 60 % of the adult population thyroid nodules are seen; however, less than 1 % of the thyroid nodules are malignant. Halo seen on ultrasound near the thyroid is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These findings show little to no variability with the findings in previous studies. 14,15,18,23,24 In our study, all cases were managed surgically through laparoscopic or open appendectomy and all the cases (n=82) recovered with no mortality. Appendectomy was complicated by surgical site infection in five patients, which was managed conservatively with broad spectrum IV antibiotics (Figure 5).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These findings show little to no variability with the findings in previous studies. 14,15,18,23,24 In our study, all cases were managed surgically through laparoscopic or open appendectomy and all the cases (n=82) recovered with no mortality. Appendectomy was complicated by surgical site infection in five patients, which was managed conservatively with broad spectrum IV antibiotics (Figure 5).…”
Section: Discussionmentioning
confidence: 82%
“…The same study also considered CECT findings of patients along with USG findings despite the fact that CECT can prove to be a major financial burden in the Indian public healthcare scenario. 14 Another study conducted in northern India by Kansakar et al, used MAS as well as USG findings to evaluate the efficacy of the combined use of both of them in predicting acute appendicitis, thus overcoming the shortcomings of study conducted by Mukhopadhyay et al 15 Our hospital is a tertiary care center situated in northwestern Uttar Pradesh in India and it receives a humongous patient load of appendicitis patients. Thus, in this study, we have tried to replicate the methodology applied by the above studies on our cohort of patients to check if the results hold true for our scenario or not.…”
Section: Introductionmentioning
confidence: 99%
“…Mukhopadhyay et al . 55 in their prospective observational study with 118 patients found that combined use of imaging with AS can prevent surgical complications and minimize NARs.…”
Section: Discussionmentioning
confidence: 99%